2017
DOI: 10.1038/srep40364
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral and peritumoral lymphatic vessel density both correlate with lymph node metastasis in breast cancer

Abstract: The status of lymph node involvement is an important prognostic factor for breast cancer. However, the presence of intratumoral lymphatic vessels in primary tumor lesions and the relationship between lymphatic vessel density (LVD) and lymph node metastasis (LNM) have not been firmly established. Therefore, we performed a meta-analysis study to investigate these issues. According to the pre-established inclusion and exclusion criteria, 13 studies, involving 1029 breast cancer patients, were included in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The peri-tumoural area supports the wound response-like process, the inflammatory response, the increased vascular density, and the permeability of the vessels of the tumour, and consists of an extracellular matrix and various cell types [29]. Peri-tumoural markers are associated with the response to neoadjuvant chemotherapy [12,30,31], hyaluronan accumulation, and lymph node metastasis [13,14,32,33], pathological biomarkers [34], prognosis [35,36], and the molecular subtype of the tumour [37]. However, the methods used to measure and extract data from the peritumoural region vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…The peri-tumoural area supports the wound response-like process, the inflammatory response, the increased vascular density, and the permeability of the vessels of the tumour, and consists of an extracellular matrix and various cell types [29]. Peri-tumoural markers are associated with the response to neoadjuvant chemotherapy [12,30,31], hyaluronan accumulation, and lymph node metastasis [13,14,32,33], pathological biomarkers [34], prognosis [35,36], and the molecular subtype of the tumour [37]. However, the methods used to measure and extract data from the peritumoural region vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…65 Multiple investigations give attention to the ITLs and PTLs, and their role in malignancy development and progression. Interestingly, Lymphovascular invasion (LVI) [66][67][68][69] and high LVDs [70][71][72] could be strongly prognostic factor for tumor aggressiveness and an indicator of occult metastases in several malignancies, including UCB as well, 13,73,74 while some retrospective analysis however controversially indicated LVDs is not associated with survival in various cancer in statistics (e.g., melanoma, breast cancer), thus, more research is needed in this part.…”
Section: The Specific Biomarkers and Growth Factors For Lymphatic Sysmentioning
confidence: 99%
“…It has been reported that there is a close relationship between increased lymphangiogenesis and metastatic spread Original Article Detection and prognostic value of intratumoral and peritumoral lymphangiogenesis in colorectal cancer in studies of other human cancers (2)(3)(4)(5)(6). For example, in head and neck cancers, malignant melanoma, and prostate and breast cancer, increased intratumoral or peritumoral lymphatic vessel density (LVD) has been found to be associated with metastatic spread and poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, thyroid papillary carcinoma, and squamous cell carcinoma of the head, neck, and esophagus, intratumoral LVD (LVDit) was predictive of lymphatic metastasis (12)(13)(14)(15). Meanwhile, peritumoral LVD (LVDpt) has been associated with lymph node metastases in cutaneous melanoma, breast cancer, prostate adenocarcinoma, and uterine cervix carcinoma (3)(4)(5)(6). However, the function of different lymphatic vessels in CRC is still elusive and controversial.…”
Section: Introductionmentioning
confidence: 99%